(untitled) (Fiep Bulletin - online, 2014)
This article is carried out by the fruit of the observation and the experiences lived as educator during 34 years of work in front of students of schools of secondary levels and students of the School of Physical Education of Córdoba, Argentina The objective of this work is to make meditate about the importance of revaluing the educational function and the professional ethics, not being this a question of the other ones but of ourselves, it should not also be alone a study and enunciated theoretical but a practice of daily life in the work of all educator.